Escrita na universidade: um estudo etnográfico acerca dos desafios do fazer científico de estudantes no ensino superior - Silveira, Letícia (2021)
Boch et al. (2015, p.11) state that the field of research on academic literacy studies is experiencing notorious growth, mainly due to the massification of higher education, in which students manifest numerous difficulties when reading and writing texts at university. Thus, during our university education, we are faced with the issue of the discourse on the literacy deficit of students entering the university, an issue that raises the production of this work. Therefore, the objective of the research presented in this master's dissertation is to investigate the challenges imposed on students by scientific writing, to understand how they engage and position themselves concerning reading and writing practices in the classroom. The study is the result of a survey conducted at a federal university in the interior of São Paulo, during the second half of 2019, in which the focus of the investigation was based on the study of literacy practices of 21 students from the Linguistics course enrolled in the discipline “Laboratório 6 – Ênfase Texto e Discurso”, in which course completion work projects were developed. For data triangulation, I introduced methods inspired by the field of ethnography, through the use of instruments determined by me during my observation in the course: field diaries, a semi-structured questionnaire, documents referring to the course, and the participants' oral productions. Consequently, I started from the study of literacy as a social practice. Furthermore, to achieve the objective proposed in this work, I considered the studies of academic literacy to understand the students' relationships with reading and writing practices in the academic context. Thus, this research's theoretical framework is mainly based on studies on academic literacy and university education (KLEIMAN, 2001; BARTON, 2007; STREET, 2003, 2010; LEA, 2001; LILLIS, 2001; FIAD, 2013 among others). The results point to the need for a dialogical approach to academic literacies, given that there are dialogical relationships triggered between the subjects participating in the classes, between genders, between social spheres, between discourses that circulate in these spheres, and between identities assumed by these subjects in their texts. Facts that exclude the speech from the deficit of writing on the part of students and highlight the sociocultural aspect of literate practices.